AMBELO (BACTRONOPHORUS THORACITES): PANGAN LOKAL TRADISIONAL ORANG KAMORO DI KAMPUNG HIRIPAU - Windy Hapsari (BALAI ARKEOLOGI PAPUA, 2013)
Kamoro ethnics are civilized society swampys area, coastal and riverine, utilizing natural products to find sources of food and other necessities. All of these capabilities is a form of adaptation and interaction with nature, and generate local knowledge passed down by their predecessors. One of the traditional local knowledge is tambelo, traditional local food source. This paper aims to find out about tambelo and benefits in the lives of Kamoro ethnics in Hiripau village. Tambelo animal mollusk is a kind of worm called latin Bactronophorus thoracites , which live on decaying wood of mangrove trees. This animal has a high nutritive substances and sources of animal protein. Tambelo very useful for Kamoro ethnic in the village Hiripau in aspects of health, social, cultural and economic.AbstrakOrang Kamoro merupakan masyarakat berbudaya rawa, daerah pantai dan muara sungai, yang memanfaatkan hasil alam untuk mencari sumber pangan dan kebutuhan lainnya. Semua kemampuan tersebut merupakan bentuk adaptasi dan interaksi dengan alam, dan menghasilkan pengetahuan lokal yang diwariskan oleh para pendahulu mereka. Salah satu pengetahuan lokal tradisional tersebut adalah tambelo, sumber pangan lokal tradisional. Tulisan ini bertujuan untuk mengetahui tentang tambelo dan manfaatnya dalam kehidupan orang Kamoro di Kampung Hiripau. Tambelo adalah hewan molusca sejenis cacing kapal bernama latin Bactronophorus thoracites, yang hidup pada kayu pohon bakau yang membusuk. Hewan ini memiliki kandungan zat bergizi tinggi dan sumber protein hewani. Tambelo sangat bermanfaat bagi orang Kamoro di Kampung Hiripau dalam aspek kesehatan, sosial budaya dan ekonomi.